Experımental Evaluatıon Of The Effects Of Magnetıc Applıances On Tooth Movement And Osteoclastıc Actıvıty - H. Ölmez; O. Meral; Ü. Gürton; D. Sağdiç (Galenos Yayinevi, 2000)
The aim of our study is to compare the effects of samarium-cobalt magnets and opening springs on tooth movement and bone histology observed in Sprague Dawley rats. Experiment is carried out on 24 female rats which are seperated into 3 equal groups. Samarium-cobalt magnets are used in the first group; opening springs are used in the second group and no force is applied in the control group. Occlusal radiograms are obtained before the experiment and at the end of the fifth day and the radiological distance between the insizomesial tips of incisors are measured. Measurements of each group are evaluated by Wilcoxon test and the differences between the groups are compared by Mann Whitney-U tests. After sacrification of rats, premaxillaes are dissected and prepared for histological examination. The number of multinuclear osteoclasts are ascertained in histological cross sections and difference between is evaluated by using Mann-Whitney"U" test. The results showed that both the magnetic appliance and opening spring were successful in tooth movement but there is no statistical differences between the magnet and spring on amount of tooth movement and bone histology.